On k-graceful labeling of pendant edge extension of complete bipartite graphs - Bhoumik, S.; Mitra, S. (Algebra and Discrete Mathematics, 2018)
For any two positive integers m, n, we denote the graph Km,n ⊙ K₁ by G. Ma Ke-Jie proposed a conjecture [9] that pendant edge extension of a complete bipartite graph is a k-graceful graph for k > 2. In this paper we prove his conjecture for n ≤ m < n² + ⎣k/n⎦ + r.